PENGEMBANGAN KOMPETENSI KEPRIBADIAN GURU DALAM MENINGKATKAN PROFESIONALISME GURU: KAJIAN LITERATUR SISTEMATIS - Rahmawati, Silvi; Salwa Salafiyah, Siti; Muhammad Sandia, Fadel; Rafani Azzam, Gattan; Mursidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Personality competence is an important aspect of teacher professionalism because it is related to integrity, emotional stability, maturity, exemplary behavior, and the quality of interaction with students. This study aims to analyze the concepts, dimensions, formative factors, development strategies, and impact of personality competence on teacher professionalism. The method used in this study is a systematic literature review by adapting the PRISMA 2020 flow. Data were obtained from SINTA-indexed journal articles and Google Scholar published from 2018 to 2025. A total of 14 articles met the inclusion criteria and were analyzed using thematic content analysis. The findings show that personality competence includes being steady, stable, mature, wise, authoritative, morally upright, polite, reflective, and exemplary. This competence is shaped by internal, external, and institutional factors. Its development strategies include character-based training, self-reflection, mentoring, coaching, learning communities, transformative supervision, and the strengthening of moral and spiritual values. This review emphasizes the importance of personality competence in developing teacher professionalism.